UJI EFEK HIPOGLIKEMIK PEMBERIAN GABUNGAN INFUSA DAUN MAJA (Aegle marmelos CORREA) DAN DAUN MAHKOTA DEWA (PHALERIA MACROCARPA SCHEFF)PADA MENCIT JANTAN (MUS MUSCULUS) - Nurshalati Tahar (Jurnal Farmasi UIN Alauddin Makassar, 2013)
The research on hypoglicemic effect test of combination administrasion infusion of the Maja leaves (Aegle marmelos Correa) and the Crown of God leaves (Phaleria macrocarpa Scheff) on the blood glucose level of mice (Mus musculus) has been done. The aim the research to know on hypoglicemic effect that has been given of combination infusion from the both plants, basicly of scientific data. In experiment 15 mice where divided in to 5 groups, each group consisted of 3 mice. The 1st group was given 1% w/v of Natrium CMC as a negative control, the 2nd group was given the crown of God leaves infusion 20% w/v, the 3rd group was given the maja leaves infusion 15% w/v, the 4th group given the combination administrasion infusion of the crown of God leaves and maja leaves and the 5th group was given the glibenclamide suspension 0,002% w/v as a positive control. The initial blood glucose level was measured 1 hour after the treatment was given every hour in 5 hours after the infuse administrasion. The result of the research showed that given of combination infusion of the Maja leaves (Aegle marmelos Correa) and the Crown of God leaves (Phaleria macrocarpa Scheff) was not significantly from the 0,002% w/v glibenclamide suspension as a positive control but it has hypoglycemic effect at the 5th hours.